2017
DOI: 10.1097/md.0000000000005724
|View full text |Cite
|
Sign up to set email alerts
|

The coexistence of SAPHO syndrome and rheumatoid arthritis

Abstract: Rational:SAPHO (Synovitis-Acne-Pustulosis-Hyperstosis-Osteitis) syndrome is a rare disease featured by its dermatological and osteoarthritic disorders, the latter of which mainly affecting the anterior chest wall, spine, and sacroiliac joint. However, rheumatoid arthritis (RA) is a chronic autoimmune disease, mainly affecting the synovial tissue of small joints in hands and feet. Here, we present an extremely rare case diagnosed with both SAPHO syndrome and RA, with an onset interval of 10 years. So far, only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“… [5] Xu et al also described a clinical case of coexistence of SAPHO syndrome and rheumatoid arthritis with an onset interval of 10 years. [4] These cases indicated that it is possible for the co-occurrence of autoimmune diseases in patients with SAPHO syndrome. Here, we first report 5 patients with concurrence of SAPHO syndrome and SS.…”
Section: Discussionmentioning
confidence: 98%
“… [5] Xu et al also described a clinical case of coexistence of SAPHO syndrome and rheumatoid arthritis with an onset interval of 10 years. [4] These cases indicated that it is possible for the co-occurrence of autoimmune diseases in patients with SAPHO syndrome. Here, we first report 5 patients with concurrence of SAPHO syndrome and SS.…”
Section: Discussionmentioning
confidence: 98%
“…AS is a chronic disease in which the spine is the main lesion site, with the involvement of the sacroiliac joints. The comorbidities of SAPHO syndrome often occur after SAPHO syndrome, and only one case of coexistence of rheumatoid arthritis and SAPHO syndrome has been reported ( 13 ). SAPHO syndrome with AS has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Barczyńska et al described the RA-AS combination in a case series of three Polish people [ 24 ]. In another study, Xu et al demonstrated an association between SAPHO (Synovitis-Acne-Pustulosis-Hyperstosis-Osteitis) syndrome and RA in a 59-year-old woman, and the duration between the two diagnoses was 10 years [ 25 ].…”
Section: Discussionmentioning
confidence: 99%